Utilization of Historical Heritage Sites as Integrated Social Science Learning at SMPN 18 Bengkulu - Setiawan Pratama, Agung; Satria, Irwan; Gilang, M. Ilham (Jurnal Pendidikan dan Profesi Keguruan, 2026)
​Social Studies (IPS) learning at SMPN 18 Bengkulu has long been dominated by lecture-based methods, leading to low student engagement with local historical content. This study aims to describe the implementation of site-based learning methods and analyze students’ responses to the utilization of historical heritage sites as Social Studies learning media. Using a descriptive qualitative approach, data were collected through observation, semi-structured interviews with teachers and students, and a document analysis. The research involved two teachers and 15 students selected purposively to represent various grade levels and achievement backgrounds. The results indicated that historical sites, such as Fort Marlborough, Soekarno’s Exile House, and Fatmawati’s House, were effectively integrated into classroom learning through structured phases of pre-visit preparation, site observation, and post-visit reflection. Quantitative data revealed notable improvements in students’ learning interest (3.1 to 4.4), conceptual understanding (3.0 to 4.2), and perceived relevance (3.2 to 4.3). The students showed high enthusiasm and deeper historical awareness through experiential learning. The novelty of this study lies in combining qualitative insights with quantitative validation to demonstrate that heritage-based learning fosters both cognitive gains and affective attachment to local culture an integration rarely emphasized in prior studies. The findings provide a replicable pedagogical framework that bridges theory and practice, and can be adapted digitally through virtual or augmented site visits. Thus, this model strengthens the relevance of contextual learning within the Merdeka Belajar curriculum and o​ffers a sustainable approach for schools with limited access to physical heritage sites.